Analysis of ship scrubbing operations and their socio-environmental impact in Peru - Ramírez Caján, Alfonso (2022)
The objective of this research was to identify the risks and impacts to the environment and public health generated by ship dismantling operations in Peru, through the shipyard and dry dock services, whose regulations are supported by the Hong Kong International Convention for the Safe and Environmentally Sound Recycling of Ships and the scrapping plans authorized by the National Maritime Authority as the supervisory and supervisory entity of these activities. In this sense, the potential danger of some chemical substances adhering to the process residues was analyzed; such as asbestos, Volatile Organic Compounds, Polychlorinated Biphenyls and lead, with bioaccumulative and biopersistent capacity to insert themselves in the trophic chain and alter their ecological niche, due to their inadequate handling and final disposal that result in risks associated with the occupational health and safety of its operators, workers and interested parties; as well as the receiving bodies converted into sinks of inorganic charge harmful.